A reliable model for gamma oscillations in hippocampal tissue. Issue 7 (24th March 2015) - Schneider, Justus; Lewen, Andrea; Ta, Thuy‐Truc; Galow, Lukas V.; Isola, Raffaella; Papageorgiou, Ismini E.; Kann, Oliver
Abstract : Gamma oscillations (30–100 Hz) reflect a fast brain rhythm that provides a fundamental mechanism of complex neuronal information processing in the hippocampus and in the neocortex in vivo. Gamma oscillations have been implicated in higher brain functions, such as sensory perception, motor activity, and memory formation. Experimental studies on synaptic transmission and bioenergetics underlying gamma oscillations have primarily used acute slices of the hippocampus. This study tests whether organotypic hippocampal slice cultures of the rat provide an alternative model for cortical gamma oscillations in vitro. Our findings are that 1) slice cultures feature well‐preserved laminated architecture and neuronal morphology; 2) slice cultures of different maturation stages (7–28 days in vitro) reliably express gamma oscillations at about 40 Hz as induced by cholinergic (acetylcholine) or glutamatergic (kainate) receptor agonists; 3) the peak frequency of gamma oscillations depends on the temperature, with an increase of ∼3.5 Hz per degree Celsius for the range of 28–36°C; 4) most slice cultures show persistent gamma oscillations for ∼1 hr during electrophysiological local field potential recordings, and later alterations may occur; and 5) in slice cultures, glucose at a concentration of 5 mM in the recording solution is sufficient to power gamma oscillations, and additional energy substrate supply with monocarboxylate metabolite lactate (2 mM) exclusively increases the peak frequency by ∼4 Hz. This study shows that organotypic hippocampal slice cultures provide a reliable model to study agonist‐induced gamma oscillations at glucose levels near the physiological range. © 2015 Wiley Periodicals, Inc.